In vitro Activity of Allicin Alone and in Combination With Antifungal Drugs Against Microsporum canis Isolated From Patients With Tinea Capitis - Zhou, Ya Bin; Xiao, Yuan Yuan; Chao, Jin Jing; Ma, Lin (Frontiers in Medicine, 2021)
The checkerboard broth method based on the Clinical and Laboratory Standards Institute M38-A3 document was used in this study to evaluate the in vitro activity of allicin alone and in combination with the antifungal drugs (griseofulvin, fluconazole, itraconazole and terbinafine) against Microsporum canis isolated from patients with tinea capitis. When allicin was used alone, only weak anti-M. canis effects were found. The MIC50, MIC90 and geometric mean (GM) of terbinafine were the lowest among the compounds tested. Synergism was observed for the combinations of allicin with itraconazole and terbinafine. Only indifference was observed for the combinations of allicin with griseofulvin and fluconazole. Our study illustrated the synergism of allicin in combination with itraconazole and terbinafine, which could be a reference for the treatment of tinea capitis due to M. canis.